Efficient Geometrical Clock Synchronization for Pairwise Sensor Systems. - Fernández-Madrigal, Juan Antonio; González-Navarro, María Ángeles; Asenjo-Plaza, Rafael; Cruz-Martín, Ana María (IEEE, 2021)
Numerous time synchronization methods have been proposed during the last decades targeted at devices transmitting in general-topology networks, e.g. wireless sensor networks. Interestingly enough, there are still sensorics applications that, from the data flow point of view, just consist of pairs of devices -typically, being one of them a central controller shared among all pairs-; this is common in embedded systems, mobile robots, factory cells, domotic installations, etc. In these cases, time synchronization takes the form of the estimation of the relative drifts and offsets of these pairs of clocks, thus the quality, guarantees and computational cost of the methods become crucial. Under that specific perspective, it is still possible to propose novel approaches that are computationally efficient while providing guarantees on the resulting estimates for the relative clocks relation. In particular, solving the synchronization problem through a geometrical interpretation is specially suitable, since it provides both efficiency and sound estimates with hard bounds. In this article we analyze a direct geometrical approach for pairwise systems that, through a more direct formulation of the common geometrical setting, improves efficiency and adapts better to diverse stochastic transmissions, while providing good estimates. We demonstrate its advantages with a real low-cost, embedded test bed that can be appropriately instrumented for measuring times, comparing its performance against previous synchronization approaches suitable for pairwise systems.
https://openpolicyfinder.jisc.ac.uk/id/publication/3570
Keywords: Sincronización; Clock synchronization; Networked sensor fusion; Sensor applications